2019
DOI: 10.4082/kjfm.17.0143
|View full text |Cite
|
Sign up to set email alerts
|

Mammary Paget’s Disease of the Nipple: Relatively Common but Still Unknown to Many

Abstract: Mammary Paget’s disease is clinically defined as skin inflammation of the nipple area and is an adenocarcinoma of the epidermis of the nipple. The pathogenesis of mammary Paget’s disease is relatively unknown; nonetheless, there are two popular theories that support the underlying carcinoma and de novo carcinogenesis. For the attending medical practitioner, mammary Paget’s disease poses a diagnostic and therapeutic dilemma, especially in the absence of a clinically palpable breast mass. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…[25] The sensitivity and specificity of dynamic contrast MRI in their study were 100% and 86% respectively for detecting malignant lesions. [7] In a study performed by Yabuuchi et al to assess the utility of a combination of dynamic contrast MRI and DWI in lesion characterization, the sensitivity was found to be 92% and the specificity was found to be 86% for differentiating benign from malignant lesions. [26] A study done by Yoshifumi Kuroki and Katsuhiro on 29 women with suspicious breast abnormalities showed that diffusion tensor imaging (DTI) may provide useful information to better characterize breast abnormalities on MRI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[25] The sensitivity and specificity of dynamic contrast MRI in their study were 100% and 86% respectively for detecting malignant lesions. [7] In a study performed by Yabuuchi et al to assess the utility of a combination of dynamic contrast MRI and DWI in lesion characterization, the sensitivity was found to be 92% and the specificity was found to be 86% for differentiating benign from malignant lesions. [26] A study done by Yoshifumi Kuroki and Katsuhiro on 29 women with suspicious breast abnormalities showed that diffusion tensor imaging (DTI) may provide useful information to better characterize breast abnormalities on MRI.…”
Section: Resultsmentioning
confidence: 99%
“…Mammary Paget disease, or adenocarcinoma of the nipple epidermis, is relatively rare but may be misdiagnosed as a benign dermatosis if care is not taken. [7] Recurrent or chronic infections, pain, and scarring are causes of morbidity. Mastitis is usually seen in lactating women, but the presence in a nonlactating woman should spur evaluation for an inflammatory carcinoma, newly onset diabetes, infection with Mycobacterium tuberculosis, and other idiopathic causes.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the reticulate pattern of adenocarcinoma in situ is very rare. Most often, MPD presents unilaterally as eczematoid, erythematous, scaly, ulcerated, bleeding or thickened skin changes with or without nipple discharge or invagination 4 . Patients are asymptomatic or report symptoms of pain, pruritus, burning and tingling 1,2 .…”
Section: Figurementioning
confidence: 99%
“…Majority of cases are associated with underlying carcinoma of breast either invasive or in situ (Dubar et al 2017). It is thought that malignant cells from intraductal carcinoma extend into the overlying epidermis through mammary duct epithelium and proliferate in the epidermis causing thickening of the nipple and areola (Ooi et al 2018). • Clinical feature: It usually manifests as a chronic eczematous change of the nipple and areola often associated with an underlying lump (Aguayo-Carreras et al 2017).…”
Section: Paget's Diseasementioning
confidence: 99%